(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The article deals with the nature of the synthesis of modern Russian prose and elements of Eastern poetics. On the example of Victor Pelevin’s texts – Т (2009), Batman Apollo (2013), Secret views of Mount Fuji (2018) – the question of functioning in the author’s artistic discourse of the designated signs is objectified. In a special way in V.O. Pelevin’s prose the religious and philosophical aspect of Zen Buddhism as the adjacent direction of East culture is played. Elements of Eastern poetics organize the plot and thematic block of works in a special way. The variant principle of Viktor Pelevin’s writing organically complements the literary process, moving in a spiral of increment of world art practice. Moreover, reading is in a situation of multiple connotations of meanings, as well as a constructive relational assessment of being. Elements of oriental poetics in Pelevin discourse acquire shades of semantic tricks. The synergy of the author’s experiment is also becoming a reception model for the potential reader. An open dialogue, thus, produces the manipulation and synthesis of cultural signs with their own halo of readings. The analysis of the prose of Victor Pelevin confirms the idea that the compilation of different aesthetically world contemplation positions expanding the horizon of meaning, reduplicate the rhizome connotations. It is concluded that the implementation of Eastern poetics in the texts of postmodernism at the level of motives and images objectively concretizes the process of cultural synthesis of modern literature. Key words: poetics of Oriental literature, modern prose, postmodernism, Victor Pelevin, cultural synthesis, aesthetics of reading. DOI 10.18522/1995-0640-2020-1-138-145